2016
DOI: 10.22289/2446-922x.v2n1a6
|View full text |Cite
|
Sign up to set email alerts
|

Transtornos Psicológicos Associados À Disfunção Temporomandibular

Abstract: RESUMOO objetivo desse estudo foi realizar um levantamento da literatura relacionada a distúrbios psicológicos associados à disfunção temporomandibular (DTM). Método: Foram encontrados, inicialmente, 634 artigos nas bases de dados Scielo, Pub Meed e Medline. As palavras chave utilizadas na busca foram: transtornos psicológicos e DTM, estresse e DTM, depressão e DTM, ansiedade e DTM. Após a leitura do resumo desses artigos, foram selecionados 30 artigos para compor o presente estudo. A seleção desses artigos se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
(18 reference statements)
0
2
0
4
Order By: Relevance
“…As previously stated, women are more prone to suffering from psychological tensions 25 . When this issue is discussed, it is known that anxiety and depression can induce or aggravate TMD symptoms 38,39 . Considering that sensitivity change 33 is a common symptom of this disorder, it can be suggested that women present this difference more often than men.…”
Section: Discussionmentioning
confidence: 99%
“…As previously stated, women are more prone to suffering from psychological tensions 25 . When this issue is discussed, it is known that anxiety and depression can induce or aggravate TMD symptoms 38,39 . Considering that sensitivity change 33 is a common symptom of this disorder, it can be suggested that women present this difference more often than men.…”
Section: Discussionmentioning
confidence: 99%
“…Fatores emocionais como estresse, ansiedade e depressão associados à presença de disfunção temporomandibular, podem levar ao desenvolvimento de hiperatividade muscular, causando dor intensa na região. Esse quadro pode evoluir com grande variabilidade, levando apenas alguns dias para aparecer à dor ou até mesmo meses e anos, tendo como agravante os hábitos parafuncionais (Braga et al, 2016).…”
Section: Definiçãounclassified
“…Entretanto, a cefaleia pode se originar de uma incidência dolorosa da ATM e músculos adjacentes. Um detalhe importante é que há mais que um tipo de cefaleia e que estas podem se associar à DTM e aos transtornos emocionais como a ansiedade, a irritabilidade, ao estresse e a depressão, sem que, precisamente, sejam a causa e consequência da DTM, apesar de tais fatores podem causar a piora da dor, do desconforto, da irritação e levar à baixa autoestima (Braga et al, 2016).…”
Section: Sinais E Sintomasunclassified
See 1 more Smart Citation
“…According to other studies report, there is a significant association between the variables pain, anxiety and depression with changes in sleep quality 6,7 . Many individuals with TMD report complaints about poor sleep quality and anxiety; however, it is not known if these symptoms are associated with TMD type [7][8][9] . In addition to the poor quality of sleep presented by the patients with TMD, a high pain sensitivity has been observed.…”
Section: Introductionmentioning
confidence: 99%